Genomic, transcriptomic, and T cell receptor profiling in stratifying response to first-line chemoradiotherapy or radiotherapy for esophageal squamous cell carcinoma - Zhang, Xiaqin; Lian, Jianhong; Chen, Fukun; Wang, Kai; Xue, Haoyuan; Jia, Sufang; Wang, Weili; Li, Zhongkang; Liang, Hua; Li, Hongwei (Frontiers in Oncology, 2025)
IntroductionEsophageal squamous cell carcinoma (ESCC) accounts for 80% of esophageal cancer (EC) worldwide. The molecular characteristics of locally advanced ESCC have been extensively studied.MethodsIn this study, we investigate the genomic and transcriptomic characteristics and try to provide the basic T-cell receptors (TCRs) dynamics and its genomic and transcriptome association during the radiochemotherapy of ESCC using multi-omics analysis.ResultsA total of 23 patients with pathologic diagnoses of locally advanced ESCC were enrolled. The median tumor mutational burden (TMB) of the 23 ESCC patients were 3.47 mutations/ Mb (mega-base). The TP53, RTK/RAS, and NOTCH pathways were concurrently prevalent in ESCC. Besides, some less prevalent pathways, including WNT and HIPPO pathways also exhibited superior frequencies in ESCC. Meantime, we found the immune-hot tumor had higher immune infiltration scores. The median TMB in the progression-free survival (PFS) low group was significantly higher than that in the PFS-high group. The chromosomal copy number variation (CNV) burden of the neutrophil-to-lymphocyte ratio (NLR)-high group appeared to be higher than that of the NLR-low group, and the StromalScore in the NLR-low group was significantly higher. Clonality score was significantly increased from pre-treat to post-treat and from on-treat to post-treat. Shannon index was significantly decreased from pre-treat to post-treat and from on-treat to posttreat. Richness was significantly decreased from pre-treat to post-treat.DiscussionMultiomics analysis provided the basic TCRs dynamics and their genomic and transcriptome association during the radio-chemotherapy of 23 locally advanced ESCC in China, and provided a valuable insights into the heterogeneity and the tumor microenvironment and treatment responses. Meantimes, the identification of biomarkers and the exploration of their association with treatment outcomes could have important implications for clinical practice.